2022
DOI: 10.1038/s41598-022-13744-7
|View full text |Cite
|
Sign up to set email alerts
|

MIF homolog d-dopachrome tautomerase (D-DT/MIF-2) does not inhibit accumulation and toxicity of misfolded SOD1

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by loss of upper and lower motor neurons. About 20% of familial ALS cases are caused by dominant mutations in SOD1. It has been suggested that toxicity of mutant SOD1 results from its misfolding, however, it is unclear why misfolded SOD1 accumulates within specific tissues. We have demonstrated that macrophage migration inhibitory factor (MIF), a multifunctional protein with cytokine/chemokine and chaperone-like activity, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In contrast, MIF and DDT play a different role in physiological processes such as adipogenesis and correlate differently with obesity [122]. D-DT has so far shown interesting results when applied in studies on spinal cord injury, amyotrophic lateral sclerosis, multiple sclerosis, tumors, skin diseases, heart failure, myocardial infarction, alveolar repair, orthotopic liver transplantation, and sepsis [61,121,[125][126][127][128][129][130][131][132][133][134].…”
Section: D-dopachrome Tautomerasementioning
confidence: 99%
“…In contrast, MIF and DDT play a different role in physiological processes such as adipogenesis and correlate differently with obesity [122]. D-DT has so far shown interesting results when applied in studies on spinal cord injury, amyotrophic lateral sclerosis, multiple sclerosis, tumors, skin diseases, heart failure, myocardial infarction, alveolar repair, orthotopic liver transplantation, and sepsis [61,121,[125][126][127][128][129][130][131][132][133][134].…”
Section: D-dopachrome Tautomerasementioning
confidence: 99%
“…Various studies have revealed that D-dopachrome tautomerase (D-DT, also known as MIF-2) is a functional homolog of MIF, since both have a similar gene structure, 3D architecture, and enzyme activity 11 , 24 26 . D-DT shares several biological activities with MIF and could therefore represent an endogenous amplifier of MIF action 21 , 27 , 28 ; however, divergent effects have also been reported 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%